YEATS domain: Linking histone crotonylation to gene regulation. Issue 1 (1st January 2017) - Li, Yuanyuan; Zhao, Dan; Chen, Zhonglei; Li, Haitao
ABSTRACT: Recent research reveals that the YEATS domains preferentially recognize crotonylated lysines on histones. Here, we discuss the molecular mechanisms that enable this recognition and the biological significances of this interaction. The dynamics of histone crotonylation and its potential roles in the regulation of gene expression will also be discussed.